2023
DOI: 10.3390/nu15040801
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Emptying of New-World Milk Containing A1 and A2 Β-Casein Is More Rapid as Compared to Milk Containing Only A2 Β-Casein in Lactose Maldigesters: A Randomized, Cross-Over Trial Using Magnetic Resonance Imaging

Abstract: Lactose maldigesters report an increase in abdominal pain due to the consumption of milk containing a mixture of A1 and A2 β-casein as compared to milk containing only A2 β-casein. Gastric transit affects gastrointestinal symptoms and rapid transit has been associated with an increase in abdominal pain. We conducted a double-blinded, randomized, crossover trial in 10 lactose maldigesters. Subjects consumed each of the two types of milk: conventional milk containing 75% A1 β-casein and 25% A2 β-casein and A2 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 33 publications
(44 reference statements)
0
8
0
2
Order By: Relevance
“…The research suggests that the difference could be a contributing factor to the higher occurrence of gastrointestinal symptoms in lactose-intolerant individuals after A1 milk consumption. Overall, lower rates of gas production and fewer digestive system disorders were observed in lactose-intolerant individuals consuming A2 milk [51].…”
Section: Lactose Intolerancementioning
confidence: 91%
See 2 more Smart Citations
“…The research suggests that the difference could be a contributing factor to the higher occurrence of gastrointestinal symptoms in lactose-intolerant individuals after A1 milk consumption. Overall, lower rates of gas production and fewer digestive system disorders were observed in lactose-intolerant individuals consuming A2 milk [51].…”
Section: Lactose Intolerancementioning
confidence: 91%
“…The A1 milk consumer group generally had higher maldigestion compared to the A2 milk group. [51] Table 1. Cont.…”
Section: Lactose Intolerance In Vivomentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous research indicated that acute consumption of A2 milk results in fewer symptoms and reduced maldigestion in lactose maldigesters [ 15 ]. Furthermore, milk containing A1 β-casein undergoes more rapid gastric transit than A2 milk, which suggests less stomach and/or small bowel digestion and more colonic fermentation [ 16 ]. Fermentation generates gases including hydrogen, carbon dioxide, and methane in some individuals and causes intestinal distention and fecal urgency.…”
Section: Introductionmentioning
confidence: 99%
“…In Ukraine, given the long tradition of cattle breeding, there is an excellent variety of different breeds, among which the unique Ukrainian Lebedyn breed, genetic studies of which began only recently [11,16].…”
Section: Introductionmentioning
confidence: 99%